2006
DOI: 10.1021/ef0503921
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chemical Composition of Coal-Based Jet Fuels on the Deposit Tendency and Morphology

Abstract: The formation of carbonaceous deposits on metal surfaces in fuel systems is a major concern for the development of advanced aircraft. This study examines the thermal stability behavior and carbon deposition and morphology of carbon deposits of thermally stressed coal-based jet fuels. These materials consisted of hydrotreated 1:1, 2:1, and 3:1 blends of refined chemical oil (RCO) with light cycle oil (LCO). Reactions were carried out in a thermal stressing reactor on an Inconel 718 surface at a 470 °C fuel temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Inconel 718 was obtained from Goodfellow Metals Ltd. (Cambridge, U.K.). The nominal composition of Inconel 718 alloy has been reported . Strips were cut and rinsed in acetone prior to use.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inconel 718 was obtained from Goodfellow Metals Ltd. (Cambridge, U.K.). The nominal composition of Inconel 718 alloy has been reported . Strips were cut and rinsed in acetone prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…The total amount of carbon deposit on Inconel strips was determined using a LECO RC-412 multiphase carbon analyzer. Conventionally, the LECO RC-412 instrument has been used to measure the amount of deposition on metal surfaces. ,, In the carbon analyzer, carbon in the deposit was oxidized to carbon dioxide by the reaction with ultra high purity (UHP) O 2 over a CuO catalyst bed. The product CO 2 was quantitatively measured by a calibrated infrared detector as a function of the temperature in the furnace.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported the effects of trace amounts of sulfur and nitrogen compounds and other contaminants such as metals [35,36], because these elements were found in large concentrations in deposits compared to fresh fuels [25]. A recent study reported that nitrogen and sulfur compounds were presented only in the liquid-phase product, but not in the solid phase deposits, and indicated that they did not aggregate during solid formation [34].…”
Section: Formation Of Solid Depositsmentioning
confidence: 99%
“…Additionally, the present upgrading processes in industry mainly aim at the cracking of a certain range of boiling points of heavy oils and the processes have to be carried out in a set of complex and expensive multi-stage reactors. [6][7][8] Therefore, several new technologies should be developed to convert the heavy and extraheavy oils into light products efficiently and environmentally.…”
Section: Introductionmentioning
confidence: 99%